Body‐temperature shape‐shifting liquid crystal elastomers. Issue 14 (28th October 2020) - Shaha, Rajib K.; Torbati, Amir H.; Frick, Carl P.
Abstract: Nematic monodomain liquid crystal elastomers (LCEs) undergo efficient temperature‐induced reversible shape‐shifting around the nematic‐isotropic transition temperature ( T ni ) due to the presence of the liquid‐crystalline order of mesogens. Usually, the T ni of nematic LCEs is much higher than the human body temperature, and therefore LCEs are not often considered for biomedical applications. This study describes an LCE system where the T ni is tuned by substitution of the rigid mesogens RM257 with a flexible backbone PEGDA250. By systematically substituting the RM257 with PEGDA250, the T ni of LCEs was observed to decrease from 66°C to 23°C. A rate‐optimized LCE material was fabricated with 10 mol % rigid mesogens substituted with a flexible backbone that demonstrated T ni at 32°C, in‐between the room temperature of 20°C and the body temperature of 37°C. The T ni allowed the programmed shape at room temperature, quick shape‐shifting upon exposure to body temperature, and before‐programmed shape when kept at body temperature. This LCE material displayed reversible length change of 23%, opacity change, and shape change between room temperature and body temperature. Abstract : Body‐temperature activated reversible shape‐shifting liquid crystal elastomer.